(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Aspergillus parasiticus, a pathogenic fungus, poses a significant threat to agriculture and human health due to its ability to contaminate foodstuffs and produce mycotoxins. The constant rise in antifungal resistance necessitates exploring alternative approaches to combat fungal infections. In this study, we investigated the potential of Cinnamomum verum essential oil as an antifungal agent against Aspergillus parasiticus using the Poisoned Food Technique. The essential oil was collected from local market and different concentrations were prepared with the help of acetone. The antifungal activity of the oil was evaluated against Aspergillus parasiticus in vitro using poisoned food assay. The minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) were determined. Our findings revealed that Cinnamomum verum essential oil exhibited significant antifungal activity against Aspergillus parasiticus.